Wireless sensing of gas in mining with web service in real time - Salamanca, Juan Mauricio; Avendaño-Fernández, Eduardo; Albarracín, Martín Edgar; Gutiérrez, Germán Andrés (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
This paper presents the development and implementation of a wireless system and sensing of explosive gases in mining with web service in real time. The system consists of modules configured in a network of sensors arranged in the inner galleries of the mine; each one of these moduleshas the ability to receive signals from sensors of methane, carbon dioxide, the charge level of battery and an auxiliary sensor. This card has a module 900 Mhz Xbee pro DigiMesh, responsible for transmitting the sensor data. This data is sent to the external module which connects with a card Beaglebone that displays data on a web platform made in Python software, in which sensor data are stored in order to analyze the behavior of gases in time. The network is implemented in a tree topology configuring modules as routers and one as a coordinator that controls the network. The modules are organizedhierarchically in order to transmit the data to the entrance of the mine. Finally, the network configuration is done until the system enters in mode sleep (idle) when it is not receiving information, in this way the consuming power decreased, increasing the autonomy of the batteries. This paper describes the design, implementation and operation of a gas monitoring system in mining with web service inreal-time based on a network of Zigbee sensors.